The effects of visual merchandising and price sensitivity on impulse purchase behaviour among young apparel shoppers in Bangladesh - Karim, Md Wasiul; Haque, A. K. M. Ahasanul; Juhdi, Nurita; ., Md Muhibbullah; Ulfy, Mohammad Arije (Conscientia Beam, 2020)
The intense competition among apparel retail outlets in Bangladesh are on the rise. Due to the increasing number of these outlets, young consumers tend to differentiate the apparel products by visiting stores and compare prices with other outlets and end up with impulse purchase. The purpose of this study is to examine the relationship between visual merchandising, price sensitivity and impulse purchase behavior among young apparel shoppers. For this purpose, the sample of 305 young shoppers in Bangladesh completed the questionnaire. Stimulus Organism and Response (SOR) model was employed. The data were analyzed by deploying partial least squares structural equation modeling (PLS-SEM). By applying two-step approach for instance, measurement model for indicator loadings, convergent validity, reliability and structural model for path analysis, the result signifies that both visual merchandising and price sensitivity positively and significantly affects shoppers’ shopping enjoyment and impulse purchase behavior, which shoppers’ shopping enjoyment positively affects impulse purchase behavior. Results also found that shopping enjoyment mediates the relationship between visual merchandising, price sensitivity and impulse purchase behavior. The findings are useful for retailers to understand the essence of impulse purchasing behavior and factors, such as visual merchandising and price sensitivity, which can have great impact on impulse purchase behaviors among consumers.